An empirical assessment of fintechs heterogeneous transmission channels to financial development among African economies - Tochukwu Timothy Okoli; Devi D. Tewari (Cogent Economics & Finance, 2020)
The poor use of innovations for financial service delivery among African banks has limited the extent of financial development in the continent. Consequently, financial authorities seeks for a technology-enabled financial solution; an area not well covered in literature. This study therefore, examines the determinants of financial development in a panel of thirty-one heterogeneous African markets for the period 2002-2019 with emphasis on financial technology (Fintech). The liquidity-preference and credit-creation theories were used to model a dummy variable interactive equation to capture possible heterogeneities. The study hypothesized that Fintech transmits directly to financial development among emerging Africa but indirectly through bank-efficiency and financial inclusion among the frontier and fragile groups, respectively. Results from both the dynamic system GMM and the static techniques support this hypothesis with significant heterogeneities in both the intercept and slope coefficients of Fintech among the various groups. The study concludes that on average, emerging African markets report higher financial depth than the frontier and fragile groups; however, with higher slopes, they can converge with emerging markets' in the long-run through Fintech adoption. The study recommends the collaboration of Fintech with banks, improved bank efficiency and financial inclusion as panaceas to promote financial development in Africa.
Keywords: G00; G10; G21; O55; 330; Africa; Bank Efficiency; Financial Development; Financial Technology